Fluorescence of 4- and 5-nitro isocarbostyryl derivatives revisited - Liudmyla Chepeleva; Andrey Doroshenko (Вісник Харківського національного університету: Серія xімія)
Spectral properties of several selected nitro substituted isocarbostyrils (I, isoquinoline-2H-1-ones) were discovered in our research group several decades ago. These relatively small molecules demonstrated unusual spectral behavior: they were highly solvatochromic and 5-nitro-I appeared fluorescent in solvents of intermediate-to-high polarity. UV-vis spectra of the title compounds were studied previously both experimentally and theoretically, however, on the quite low level of quantum theory (π-electronic approximation). The aim of the current communication is to reconsider them on DFT/TDDFT level with the account of the nπ* states localized on NO2-group spin-orbit coupling analyses and radiationless intersystem crossing (ISC) process, which regulates the fluorescent properties of nitro-substituted aromatic compounds.